Respons Mahasiswa Terhadap Pengembangan Nilai-Nilai Karakter Setelah Mengimplementasikan Pembelajaran Matematika Yang Mengintegrasikan Nilai-Nilai Islam - Masandhy, Chyndhy Indra; , Masduki, S.Si, M.Si (2015)
Abstract: This study aims to describe the student's response to the development of character values after implementing the mathematics learning that integrates the values of Islam. Informants of this study is the first semester students of class A in Mathematics Education Department of UMS. Data are collected by using interviews and questionnaites as the main method, the method aids in the form observation and documentary. This study uses a qualitative descriptive method. The data validity are done by triangulation source, triangulasi technique and triangulation method. Analysis of qualitative data through 3 steps, namely data reduction, data presentation, and conclusion. The results show the student's response to the development of character values after implementing the mathematics learning that integrates the values of Islam are, (1) The process of implementation of the values of the characters in the learning of mathematics include greeting and prayer before and after the study; giving encouragement to students; developing a religious attitude, honesty, tolerance, discipline, hard work, creative, democratic, curiosity in learning, exemplary behavior, (2) the need to develop the character value in the learning because the values of the character can show a student excellence as a thinker who has superior intellectual, (3) student responses after following a basic math learning makes the students have better understanding the value of personality in themselves.